A study on chronic obstructive pulmonary disease and its determinants among underground coal mine workers in Bankola area, Durgapur, West Bengal - Hasibur Zaman Haque; Sanjoy Kumar Sadhukhan; Jayita Pal; Nandu Krishna (International Journal Of Community Medicine And Public Health, 2024)
Background: Chronic obstructive pulmonary disease is a leading cause of morbidity and mortality worldwide that effectuate an economic and social burden that is both considerable and progressive. Mortality from respiratory disease remains an important occupational hazard among coal miners. Inhalation of coal mine dust is known to cause several respiratory diseases including COPD. The current study aimed to estimate the prevalence of COPD among coal miners and to find out the predictors of the same in Bankola Area, Durgapur, West Bengal. Methods: A cross-sectional study was conducted among 315 coal miners selected by simple random sampling from the list of mines in Bankola Area, Durgapur, West Bengal. The required data was collected by face-to-face interview with the help of a predesigned pretested questionnaire and subsequently clinical examination along with spirometry in an eligible subset of population. Data thus collected had been analysed by SPSS 16.0 version. Results: Prevalence of COPD among mines was found to be 11.7%. Most of the miners showed obstructive pattern, had Grade 2 severity of airflow limitation (43.2%) whereas 8.2% had Grade 4 severity. Multivariate analysis revealed that miners who were smoking for more than 20 years, working in highly dusty areas and those who were working at coal face had higher odds of developing COPD. Conclusions: Addressing substance use as well as improvement in working environment including use of personal protective equipment can holistically lead to better respiratory health of the miners.